SENTINEL LYMPH NODE BIOPSY: HISTORY AND CURRENT CONCEPTS - A. Kh. Ismagilov; N. G. Asnina; G. A. Azarov (ABV-press, 2018)
The present review is devoted to the concept of sentinel lymph node biopsy, which is an increasingly recognized method that was included into the guidelines for surgical treatment of various tumors developed by the European Organisation for Research and Treatment of Cancer (EORTC). Since the implementation of organ preservation surgeries, lymph node biopsy is considered the second most significant achievement in surgical treatment of breast cancer, because it reduces the frequency of complications (which often occur after axillary-subclavian lymphadenectomy), duration of hospital stay and treatment expenditures.